Biflavones and triterpenoids isolated from Ouratea castaneifolia (DC.) Engl., Ochnaceae - NASCIMENTO, Luís Adriano Santos do (2011)
This paper presents the chemical investigation of the leaves and stems of Ouratea castaneifolia (DC.) Engl.. There are no chemical or pharmacological studies with this species. Classic phytochemical investigation of the organic extracts together with high pressure liquid chromatography (HPLC) procedures lead to the identification of seventeen metabolites: seven triterpenes (friedelin, 3β-friedelinol, α-amyrin, β-amyrin, lupeol, germanicol and taraxerol), four steroids (sitosterol, stigmasterol and the glycosides sitosteryl 3-O-β-D-glucopyranoside and stigmasteryl 3-O-β-D-glucopyranoside), one isoflavone (5,7,4’-trimethoxyisoflavone), one flavone (5,4’-dihydroxy-7,3’,5’-trimethoxyflavone) and four biflavones (amenthoflavone, 7,7”- O-dimethylamenthoflavone, heveaflavone and tetramethylamenthoflavone). The structures of the compounds were established by the analysis of 1H, 13C NMR spectra including bidimensional techniques. The classes of the identified metabolites are in agreement with previous studies of the Ouratea genus.